Exploration of Life Skills through Researcher Generated Cartoons - Augustine, Teena; Brahme, Milind (INDIAN EDUCATIONAL REVIEW, 2013)
Visual methods are a marginalised area in the field of research methods in education. The use of cartoons within this field is even more negligible. The use of photo elicitation and audio-visual techniques often takes precedence over techniques such as cartoons. As compared to interactive audio-visual software and animation, the use of 2D images is a challenge for researchers working among primary school children. This paper deals with the possibility of using cartoons as a tool to understand the life skills of pre-adolescents. It discusses methodological issues that arise while using visual methods in dealing with sensitive issues, especially with such young respondents. This paper also discusses how researcher-generated cartoons were created and the problems encountered in administering, seeking permission from authorities and ethical issues related to the use of cartoons. It highlights the usefulness of such methods in educational research, when carried out taking the cultural values and beliefs of the setting into consideration